Anniversaries in the history of morphology in 2012. - Kutya, S. A. (Морфологія / Morphologia / Morfologìâ, 2012)
375 years ago Jan Swammerdam was born (Jan Swammerdam, 1637-1680) - Dutch naturalist, one of the founders of scientific microscopy. He graduated from Leiden University in 1663. In 1667 he defended his thesis on the breathing of animals. The author of many discoveries: demonstrated the presence of valves in lymphatic vessels, ovarian follicles, white blood cells in the blood, the first correctly explained the mechanism of penile erection and the appearance of hernias, showed that with muscle contraction its shape changes, but not size. He developed a new method of preparation, proposed a number of dissecting instruments, first began to apply the method of injecting vessels with hot wax. He designed instruments for recording the work of the heart, respiratory movements, muscle contractions with nerve irritation, etc. Basic works on the anatomy of humans and animals, especially insects, as well as mollusks, amphibians, etc. He proposed the classification of insects (subdividing them into 4 groups) based onpeculiarities of their metamorphosis.